Trade for nature - Carl-Erik Schulz; Edward B. Barbier (Fondazione Eni Enrico Mattei (FEEM), 1997)
Optimal management of biodiversity at the national level, even if achievable, is not necessarily consistent with a global optimum. While the existence of trading relationships allows for the possibility of the use of trade interventions as a means of imposing unilateral solutions, the presence of unidirectional global externalities suggests as an alternative policy the use of international transfers to achieve a co-operative solution. The following paper develops a two-country comparative trade model in which one country contains a biological resource that it exploits for domestic consumption or export while simultaneously converting habitat land for use in other economic activities. The second country does not have any stocks of this resource but values its global conservation. The latter country also produces a consumption good which it is willing to trade for the harvested resource exports of the first country. Trade has a direct effect on conservation of the biological resource through impacts on exports and thus harvesting levels, as well as an indirect effect through substitution of imports for consumption activities that lead to the conversion of habitat. We use this model to explore how national trade policy behaviour distorts the management of a biological resource, and in particular fails to achieve a global or 'cosmopolitan' optimum. We demonstrate the effects of trade policy interventions that influence the terms of trade (TOT), and international transfers that are 'neutral' with respect to the TOT. The possibility of a 'trade for nature' agreement, including free trade in exchange for a cosmopolitan stock of the resource, is discussed. It is argued that this is an option when two conditions are fulfilled: neither free trade nor an optimal tariff must be a safe option for any of the countries; and the optimal tariff on the resource products must be positive.
Keywords: Q20; F13; 330; Biodiversity; Biological resource; Cosmopolitan solution; Habitat; International transfers; Nationalist solution; Trade interventions; Terms of trade; Außenwirtschaftstheorie; Erneuerbare Ressourcen; Terms of Trade; Wohlfahrtstheorie; Theorie